Crowdfunding a monthly income: An analysis of the membership platform Patreon - Tobias Regner (Friedrich Schiller University Jena, 2019)
Membership platforms allow creators to crowdfund a monthly income, while campaigns on conventional reward crowdfunding portals aim to reach a specified funding target within a pre-set period. We study transaction-level data from Patreon, the biggest membership platform, to gain insights about behavioral patterns at this emerging type of crowdfunding. Our analysis shows that hundreds of creators crowdfund a sizable income (more than 2,500 monthly). We also find that measures of communication quality are determinants of project success, in line with the related literature. Funding dynamics - pledges as well as deletions - are heterogeneous across campaigns. Our analysis suggests that the option to delete the monthly pledge to a creator at any time serves as a feedback mechanism. We conclude that crowdfunding a monthly income offers the creative class a viable alternative to advertising-based business models.
Keywords: D90; G23; L26; L82; L86; 330; crowdfunding; Patreon; funding dynamics; cultural goods; membership platform